The interaction field a revolutionary way to create shared value for your business - Joachimsthaler, Erich 1956- (PublicAffairs, 2020)
The interaction field model: how to create unstoppable velocity -- How John Deere is revolutionizing an industry -- The new consumer and how to reach her: interactions vs. transactions -- LEGO: framing the interaction field -- Klöckner: an old-line company acts like a start-up -- Discovery and Flatiron Health reshape an entire industry -- GoPro-feeding the virtuous cycle -- Mobility in a superfluid market -- Fashion: -Burberry flips the model...and then flips out -- Velocity versus clicks: on becoming an interaction field company -- Conclusion: new ways forward-the world is created through interactions
Includes bibliographical references and index
Keywords: Interaktion; Unternehmensplanung; Kooperation; Beziehungsmarketing / (DE-627)091354323 / (DE-2867)19133-0; Kundenzufriedenheit / (DE-627)09137328X / (DE-2867)24785-4; Corporate Social Responsibility / (DE-627)091406137 / (DE-2867)25822-5; Social responsibility of business; Consumer satisfaction; Customer relations